Anaesthetic management of two cases of peripartum cardiomyopathy - Bhawna Soni; P L Gautam; Anju Grewal; Harminder Kaur (Wolters Kluwer Medknow Publications, 2011)
Anaesthetic management for caesarean section of a patient with peripartum cardiomyopathy (PPCM) can be challenging. In this case report, we describe the anaesthetic management of two cases of PPCM posted for emergency caesarean section. Anaesthetic management was directed towards optimization of myocardial contractility, preload and after load. No adverse events or complications were observed.